Uveal Melanoma - Vasilios P. Papastefanou; Victoria M. L. Cohen (Journal of Skin Cancer)
Uveal melanoma is the most common primary intraocular malignancy and the leading primary intraocular disease which can be fatal in adults. In this paper epidemiologic, pathogenetic, and clinical aspects of uveal melanoma are discussed. Despite the advance in local ocular treatments, there has been no change in patient survival for three decades. Development of metastases affects prognosis significantly. Current survival rates, factors predictive of metastatic potential and metastatic screening algorithms are discussed. Proposed and emerging treatments for uveal melanoma metastases are also overviewed. Current advances in genetics and cytogenetics have provided a significant insight in tumours with high metastatic potential and the molecular mechanisms that underlie their development. Biopsy of those lesions may prove to be important for prognostication and to allow further research into genetic mutations and potential new therapeutic targets in the future.